NAOH FROM BITTERN SOLUTION WITH MEMBRANE CELL ELECTROLYSIS PROCESS - Ardana, Danila Rorenzya; Anggraeni, Aurel Oktaviola; Redjeki, Sri (Jurnal Teknik Kimia, 2025)
Bittern is waste from seawater evaporation in the salt industry. Bittern waste contains various ions, some of which are macro and micro nutrients such as Mg2+, Na+, K+, Ca2+ and Cl- ions. The Na+ ions contained in bittern can be used to produce Sodium Hydroxide (NaOH). To reduce the negative impact of waste on the environment and increase the economic value of liquid waste from the salt making process, bittern is processed into NaOH through a membrane cell electrolysis process. The electrolysis process is carried out using a cation membrane. This method is carried out using two operating conditions that are varied, namely voltage (voltage) 6 volts; 8 volts; 10 volts; 12 volts; and 14 volts and electrolysis time is 1 hour; 1.5 hours; 2 hours; 2.5 hours; and 3 hours. The Na+ ion content in bittern is 25933.5 mg/L. The best result of this study was the formation of NaOH deposits with a content of 15.53% at a voltage of 12 volts and an electrolysis time of 1 hour.